Sport and the pandemic : perspectives on Covid-19's impact on the sport industry - Pedersen, Paul Mark; Ruihley, Brody J.; Li, Bo; Routledge (Firm) (New York : Routledge, 2020)
"This book takes a close look at how the sport industry has been impacted by the global Coronavirus pandemic, as entire seasons have been cut short, events have been cancelled, athletes have been infected, and sport studies programs have moved online. Crucially, the book also asks how the industry might move forward. With contributions from sport studies researchers across the world, the book offers commentaries, cases, and informed analysis across a wide range of topics and practical areas within sport business and management, from crisis communication and marketing to event management and finance. While Covid-19 will inevitably cast a long shadow over sport for years to come, and although the situation is fast-evolving and the future is uncertain, this book offers some important early perspectives and reflections that will inform debate and influence policy and practice. A timely addition to the body of knowledge regarding the pandemic, this is an important resource for researchers, students, practitioners, the media, policy-makers, and anybody who cares about the future of sport"--
Overview of perspectives on a global pandemic's impact on the sport industry / Paul M. Pedersen, Brody J. Ruihley and Bo Li -- Part 1. Managerial reflections -- Part 2. Marketing and communication perspectives -- Part 3. Governance during the pandemic -- Part 4. Spectatorial and participatory aspects -- Part 5. Sociological and psychological reflections.
OCLC-licensed vendor bibliographic record.
Keywords: Sports administration; Sports -- Social aspects; Sports -- Safety measures; Risk management; Crises